Low-frequency Stick-slip of A Creep Groan on A Simple Caliper-slider Experimental Model - Zahrul Fuadi (Jurnal Teknik Mesin Unsyiah, 2012)
This paper discussed a preliminary study of low-frequency stick-slip of a creep groan using a simple caliper-slider model. The experiment model is constructed based on the real operating system behind a vehicle braking system. The model consists of a sliding bar, a caliper and an arm. The analysis shows that the main frequency of generated low-frequency stick slip of the creep groan is 100 Hz with sound pressure level of 70 dB. It is found that the low-frequency stick-slip motion the result of the vibration in tangential direction. The frequency of the generated stick-slip is close to the bending natural frequency of the system. Several parameters that are important in the generation of the low-frequency of stick –slip are the sliding velocity and the contact roughness. Therefore, further study of creep groan should take into account these important parameters as well as other operating parameters.